2020
DOI: 10.3389/fimmu.2020.607541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Fully Automated Antinuclear Antibody Indirect Immunofluorescence Assay in Routine Use

Abstract: Indirect immunofluorescence assay (IFA) using HEp-2 cells as a substrate is the gold standard for detecting antinuclear antibodies (ANA) in patient serum. However, the ANA IFA has labor-intensive nature of the procedure and lacks adequate standardization. To overcome these drawbacks, the automation has been developed and implemented to the clinical laboratory. The purposes of this study were to evaluate the analytical performance of a fully automated Helios ANA IFA analyzer in a real-life laboratory setting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To overcome labor-intensive and time-consuming clinical work-up procedures and to minimize the variation of pattern and titer estimates, automated reading systems have been proposed. Furthermore, recent studies have demonstrated agreement with conventional IIF interpretation in some cases with a hit rate close to 100% in samples with a clearly negative or positive ANA tests result [ 22 , 24 , 25 ]. However, automated pattern recognition is limited to a few main IIF patterns, to date, and not used in routine practice.…”
Section: Methodological Aspects Related To the Identification Of Ssc ...mentioning
confidence: 77%
“…To overcome labor-intensive and time-consuming clinical work-up procedures and to minimize the variation of pattern and titer estimates, automated reading systems have been proposed. Furthermore, recent studies have demonstrated agreement with conventional IIF interpretation in some cases with a hit rate close to 100% in samples with a clearly negative or positive ANA tests result [ 22 , 24 , 25 ]. However, automated pattern recognition is limited to a few main IIF patterns, to date, and not used in routine practice.…”
Section: Methodological Aspects Related To the Identification Of Ssc ...mentioning
confidence: 77%
“…The anti-nuclear antibody (ANA) test was performed on a Helios automated indirect immunofluorescence assay analyzer using the ANA Hep-2 standard kit (Aesku Diagnostics, Wendelsheim, Germany). The sensitivity and specificity of this assay were reported as 73.3% and 99.4%, respectively [ 13 ]. Autoantibodies including Smith, ribonucleoprotein, Ro/SS-A, La/SS-B, nucleosome, histone, and ribosomal-P autoantibodies were assessed by standalone ELISA using a commercial kit (Alegria; ORGENTEC Diagnostika GmbH, Mainz, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, efforts are being made for automation, but there are still many restrictions. 9 Particularly, the referral to rheumatology for the sole reason of positive ANA tests has been frequently criticized as an unnecessary waste of health care resources. 7 10 In response to these issues, a “Choosing wisely” campaign has recently emerged worldwide.…”
Section: Introductionmentioning
confidence: 99%